2004
DOI: 10.1128/cdli.11.3.532-537.2004
|View full text |Cite
|
Sign up to set email alerts
|

2F3 Monoclonal Antibody Recognizes the O26 O-Antigen Moiety of the Lipopolysaccharide of Enterohemorrhagic Escherichia coli Strain 4276

Abstract: Enterohemorrhagic Escherichia coli (EHEC) and enteropathogenic E. coli (EPEC) organisms are groups of pathogenic strains whose infections are characterized by a typical lesion of enterocyte attachment and effacement. They are involved in enteric diseases both in humans and in animals, and EHEC strains can be responsible for hemolytic uremic syndrome in humans. Previously, it was shown that the 2F3 monoclonal antibody (MAb) is specific for the O26 EHEC and EPEC strains (P. Enterohemorrhagic Escherichia coli (EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Forty-four strains were isolated from the feces or intestines of young calves (1 non-EPEC/non-EHEC, 18 EPEC, and 25 EHEC strains), and 33 strains were isolated from humans (4 non-EPEC/non-EHEC, 10 EPEC, and 19 EHEC strains). Most of the strains had been described previously (37), but their pathotype (EPEC or EHEC) and serotype O26:H11 status were confirmed by PCR for the stx 1 , stx 2 , eae, EHEC hlyA, wzx-wzy O26 , and fliC H11 genes (Table 1) (10,13,15).…”
Section: Methodsmentioning
confidence: 99%
“…Forty-four strains were isolated from the feces or intestines of young calves (1 non-EPEC/non-EHEC, 18 EPEC, and 25 EHEC strains), and 33 strains were isolated from humans (4 non-EPEC/non-EHEC, 10 EPEC, and 19 EHEC strains). Most of the strains had been described previously (37), but their pathotype (EPEC or EHEC) and serotype O26:H11 status were confirmed by PCR for the stx 1 , stx 2 , eae, EHEC hlyA, wzx-wzy O26 , and fliC H11 genes (Table 1) (10,13,15).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work with Mab 2F3 has demonstrated that its target antigen was in the lipopolysaccharide domain, and that it was nonreactive to a small collection of non‐AEEC O26 strains from human (4), pig (1), poultry (1) and cattle (1) (Szalo et al. 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work with Mab 2F3 has demonstrated that its target antigen was in the lipopolysaccharide domain, and that it was nonreactive to a small collection of non-AEEC O26 strains from human (4), pig (1), poultry (1) and cattle (1) (Szalo et al 2004). Although Mab 2F3 reactive non-AEEC O26 isolates were not detected in a previous examination of the use of the capture/enrichment sELISA Rhamnose + antibiotics* eae +ve/VT +ve 9 9 2 3 0 0 eae +ve/VT )ve 11 10 7 10 10 8 (3 · NG ) eae )ve/VT )ve 10 9 2 0 5 2 (7 · NG) Total 30 28 11 13 15 10 (10 · NG) *Rhamnose agar containing cefixime (0AE05 mg l )1 ) and potassium tellurite (2AE5 mg l )1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the strains had been described previously [37,38] and their pathotype (EPEC or EHEC) and serotype O26:H11 had been confirmed by PCR for stx1, stx2, eae, wzx-wzy O26 and fliC H11 genes [39-41]. …”
Section: Methodsmentioning
confidence: 99%